AB0997 IS HEIGHT ADJUSTMENT NECESSARY IN PEDIATRIC DENSITOMETRY IN ALL CHILDREN?. (2nd June 2020) - Magallares López, B. P.; Park, H.; Cerda, D.; Betancourt, J.; Fraga, G.; Boronat, S.; Gich, I.; Marín, A. M.; Herrera, S.; Malouf, J.; Casademont, J.; García-Guillén, A.; et al.
Abstract : Background: The current guidelines of the International Society for Clinical Densitometry (1) recommend that in children with linear growth or maturational delay, Z score results should be adjusted. Height for age Z score (HAZ) adjustment is valid and can be calculated using the formula the formula proposed by Zemmel et al(2). It is possible that pediatric populations without linear growth or maturational delay, also benefit from HAZ, to prevent bone size from influencing the final Z score. Objectives: To evaluate Z score variability adjusted and without adjusting for height for age. Methods: We analysed data from densitometry performed on patients 2-20 years of age, from 2016 to 2018, assessed in the pediatric rheumatology office of our hospital for presenting risk factors for low bone mass/osteoporosis. The HAZ was calculated according to Zemel's formula. Results: Data from 103 patients are presented. Its characteristics are summarized in Table 1 When comparing these measures with their HAZ adjusted equivalents, we observe: HAZ adjusted ZsS vs ZsS without adjusting: There were no differences between their averages (p=0, 913) with a correlation coefficient of 0, 78 (p<0, 001). Concordance index at cut-off point for LBM was 0, 498, with a discrepancy of 7%, where 2% had LBM according to HAZ adjusted ZsS, but not to ZsS without adjusting. HAZ adjusted ZsWB vs ZsWB without adjusting: There were no differences between their averages (p=0, 367) with a correlation coefficient of 0, 82 (p<0, 001). Concordance index at cut-off point for LBM was 0, 557, with a discrepancy of 7%, where 2% had LBM according to HAZ adjusted ZsWB, but not to ZsWB without adjusting. Conclusion: There are discrepancies at the LBM cut-off point depending on the HAZ adjustment. The pediatric population without linear growth or maturational delay, can also benefit from HAZ adjustment, especially those with high height percentiles in which their size can hide a diagnosis of LBM. References: [1]Weber DR, Boyce A, Gordon C, Hogler W, Kecskemethy HH, Misra M, et al. The Utility of DXA Assessment at the Forearm, Proximal Femur, and Lateral Distal Femur, and Vertebral Fracture Assessment in the Pediatric Population: 2019 ISCD Official Position. Journal of clinical densitometry: the official journal of the International Society for Clinical Densitometry. 2019;22(4):567-89. [2]Zemel BS, Leonard MB, Kelly A, Lappe JM, Gilsanz V, Oberfield S, et al. Height adjustment in assessing dual energy x-ray absorptiometry measurements of bone mass and density in children. The Journal of clinical endocrinology and metabolism. 2010;95(3):1265-73. Disclosure of Interests: None declared